Childminder competence profile - recognizing, valuing, empowering - Brito, Ana Teresa (2023)
In this article, the ValChild Profile of Competences for Childminders is presented, clarifying the basis of its construction and the relevance of its definition for the professionalism of childminders in Europe. Today there is robust evidence about the early years of life for children's well-being, development, and learning. We know that positive interactions and experiences are fundamental in building a strong brain architecture and that the empowerment and training of professionals contributes decisively to a safe, nurturing, and warm environment. The quality response that childminders can give to children and families has, in this context, a special relevance. The profile was drawn up considering European benchmarks, emphasizing the Portuguese. Within the scope of the project, its recognition by specialists is underlined. From its five main areas, the competences to which they point and the systemic axes that characterize them are highlighted. The final part of the report places the Profile proposal into perspective in the light of Early Childhood Education in Portugal, stressing the relevance of the continuity of its improvement, as a tool to support the quality of the professionalism of childminders, namely through training and accreditation of competences.